The impact of fiscal policy on the underprivileged population in Indonesia - Damai, Andrianus; Aprianti, Yesi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study examines the impact of government spending across various sectors on poverty in Indonesia, motivated by the need to understand how fiscal policies affect the well-being of people experiencing poverty. Using Ordinary Least Square (OLS) and Least Square Dummy Variable (LSDV) models, the findings reveal that government spending on public services, health, education, and social protection significantly affects the number of poor people. However, spending on public services and education shows a positive coefficient, which may result from mandatory spending regulations not directly aimed at improving welfare. In contrast, government spending in the economic sector has an insignificant impact on poverty, indicating that the effects may require more than one period to manifest. Further analysis is necessary to explore this relationship. The consistency of the results was enhanced by incorporating district/city status as a predictor. These findings highlight the need for a more targeted approach to government spending to reduce poverty in Indonesia effectively.